2022
DOI: 10.3390/ijms232213930
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Endogenous Retroviruses and Inflammatory Mediators in Female and Male Offspring in a Mouse Model of Maternal Immune Activation

Abstract: Maternal infections during pregnancy and the consequent maternal immune activation (MIA) are the major risk factors for autism spectrum disorder (ASD). Epidemiological evidence is corroborated by the preclinical models in which MIA leads to ASD-like behavioral abnormalities and altered neuroinflammatory profiles, with an increase in pro-inflammatory cytokines and microglial markers. In addition to neuroinflammatory response, an abnormal expression of endogenous retroviruses (ERVs) has been identified in neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Specifically, we demonstrated that the prenatal exposure to Poly I:C in C57BL6/J mice induced a tissue-specific expression of several ERVs, ERV-related genes and inflammatory mediators with ERVs as the main carriers of the peculiar profile found in brain areas from Poly I:C mice. In addition, Poly I:C induced larger effects on the expression of some retroviral elements only in pre-frontal cortex from female offspring reinforcing the view on sex bias as a possible risk factor for ASD [136].…”
Section: Human Endogenous Retroviruses In Neurodevelopmental Disordersmentioning
confidence: 61%
“…Specifically, we demonstrated that the prenatal exposure to Poly I:C in C57BL6/J mice induced a tissue-specific expression of several ERVs, ERV-related genes and inflammatory mediators with ERVs as the main carriers of the peculiar profile found in brain areas from Poly I:C mice. In addition, Poly I:C induced larger effects on the expression of some retroviral elements only in pre-frontal cortex from female offspring reinforcing the view on sex bias as a possible risk factor for ASD [136].…”
Section: Human Endogenous Retroviruses In Neurodevelopmental Disordersmentioning
confidence: 61%
“…Researchers investigate how maternal immune activation affects fetal brain development and whether this impact is related to ASD ( 75 ). Specifically, this context has piqued interest in inflammation-related cytokines and immune molecules ( 76 , 77 ). Recent research suggests that the relationship between maternal immune activation and ASD may involve interactions between genetics and the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Type I interferons are crucial in the innate immune response to HERVs. They are produced in response to recognizing HERV-derived single-stranded RNA (ssRNA) or dsRNA by PRRs [59][60][61]. These interferons inhibit HERV replication and expression, thereby limiting their activity.…”
Section: Interaction Between Herv and The Innate Immune Systemmentioning
confidence: 99%
“…Prostate cancer -HERVs could potentially serve as diagnostic or prognostic biomarkers for prostate cancer due to antibody response [61,123].…”
Section: Melanomamentioning
confidence: 99%